PENGEMBANGAN LKS BERBASIS QR CODE DALAM PEMBELAJARAN IPA PADA SISWA KELAS IV DI SD NEGERI 2 TEGAL REJO - Cahyana, Clara Dea; Mulyono, Dodik; Frima, Aren (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to produce Qr Code Based LKS in Science Learning for Class IV Students at SD Negeri 2 Tegal Rejo that are valid, practical and effective. This type of research is Research and Development with a 4-D development model. The subjects of this research were class IV students at SDN 2 Tegal Rejo. Data collection techniques use questionnaires, tests and documentation. Based on the validation results of Qr Code Based LKS based on the assessment of language, material and media experts, it shows that Qr Code Based LKS meets the valid criteria of 0.75 for language experts, 0.93 for material experts, 0.92 for media experts. Recapitulation with an average score of 0.87. Meanwhile, from the analysis of teacher and student practicality sheet assessments, it was found that the development of Qr Code-based LKS met the practical criteria with an average score of 96.67%. In the field test, the N-gain (g) was obtained at 0.77 with a high classification, which means that the Qr Code-based LKS has high effectiveness. Based on the research results, it can be concluded that the development of Qr Code-based worksheets has proven to be valid, practical and effective in science learning for class IV students at SDN 2 Tegal Rejo so it is suitable for use. Keywords: Development, LKS, Qr Code, IPA